Nuruddin Al-Raniry Dan Sikapnya Terhadap Pluralitas Pemahaman Agama - Z Zuhelmi (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2017)
The study will explain the idea of Shaikh Nur al-Din ar-Raniry on the plurality of religious understanding. This research is important because al-Raniry is one of the great scholars who had devoted himself to the Kingdom of Aceh Darussalam in the 17th century and has inherited a number of works in various disciplines of science. Even to this day, his work still has influence among the current generation. This study aims to relate between the opinions of ar-Raniry and the understanding of the Muslim community of Aceh in the 21st century on the plurality of religious understanding. This research shows that Nur al-Din ar-Raniry is a scientist who has no tolerance to the plurality of religious teachings. He is famous as an orthodox scholar who adheres to the rules of fiqhiyah and denies the experiences of the ruhaniyah contained in the realm of Sufism. Among his fatwas which show his view is that he insulted the holy book of non-Muslims and literary works which he deemed to have no benefit. In addition, he also issued a fatwa that the teachings of wahdatul wujud being practiced and disseminated by Hamzah Fansuri and his disciples is a heretical and misleading doctrine, even the followers of these teachings are lawfully killed. His intolerance attitude, as it is in his works, is still studied by most of the Muslim community in Aceh. During the authors' observation of the religious attitudes of the Acehnese people, the authors also find the equation between Ar-Raniry's attitude and the contemporary majority of contemporary Acehnese Muslims who are not open to the plurality of religious understanding and tend to mislead other groups with differing views. It has created internal conflicts among the people of Aceh and has become an obstacle to nation and state development